Studi Penentuan Kinerja Pengelolaan Das Di Sub Das Konto Hulu - Wibowo, Anggara Cahyo; Sayekti, Rini Wahyu; Rispiningtati, Rispiningtati (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
At the Sub Konto watershed upstream, Malang Regency, the success of watershed management was certainly related to the analysis of watershed sustainability performance indicators. Key performance indicators of sustainable management of watersheds in the region was covered environmental sustainability (land use and water management) as well as the sustainability of social, economic, and institutional. Therefore, an increase in cultivation area function requires integrated planning that some watershed management goals and objectives achieved, such as: 1) soil erosion control, 2) optimal water yield, and 3) productivity and carrying capacity of the land preserved. Thus land degradation can be controlled and wellbeing of the community can be assured. The purpose of this study was to determine the performance of sustainability in watershed management upstream Sub Konto watershed, and to know the results of the classification index parameters examined include land cover, land use suitability, erosion index, coefficient of river regime, the coefficient of variance, index of water use, sedimentation, runoff coefficient in Sub Konto watershed upstream. From this study it can be seen the results of the classification and calculation of the average in 2003 - 2012 include indices for land cover classification were 45.71% medium, the suitability of the land use classification of 85.21% good, erosion index of 85.98 classifications medium, the coefficient regime river classification either 8.88 good, coefficient variance of 0.18 medium, classification, water use index of 0.34 good classification, sedimentation of 2.23 medium classification ,runoff coefficient of 0.52 bad classification on the Sub Konto watershed upstream.Keywords: DAS, erosion, land use